Business Intelligence systems in academia: A Practical Application in Universidade Católica Portuguesa - Oliveira, Pedro Manuel dos Santos Ferreira de Brito (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence